1994
DOI: 10.1063/1.358438
|View full text |Cite
|
Sign up to set email alerts
|

Probing porous media with first and second sound. II. Acoustic properties of water-saturated porous media

Abstract: The ultrasonic properties (reflection/transmission and bulk attenuation/speed) of porous and permeable media saturated with a Newtonian fluid, namely water, are considered. The frequency dependence of the transmission amplitudes of pulses is measured through a slab of thickness d1, repeated for another slab of thickness d2 for a given material. With these two measurements on two different thicknesses, it is possible in principle to separate bulk losses from reflection/transmission losses for compressional wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 22 publications
4
63
0
1
Order By: Relevance
“…Berryman (1980) has found that the predicted body-wave velocities are in very good agreement with the experimentally observed values for all three body wavemodes. For the frequency-dependent attenuation of the P 2 -mode Johnson et al (1994) have found excellent agreement between theory and experiment. In addition, for the reflection coefficients as predicted by Biot's theory they have observed reasonably good agreement between the predicted and measured frequency-dependent coefficients at ultrasonic frequencies, for all three body wavemodes.…”
Section: Materials Characterization (Inverse Problems)mentioning
confidence: 55%
See 2 more Smart Citations
“…Berryman (1980) has found that the predicted body-wave velocities are in very good agreement with the experimentally observed values for all three body wavemodes. For the frequency-dependent attenuation of the P 2 -mode Johnson et al (1994) have found excellent agreement between theory and experiment. In addition, for the reflection coefficients as predicted by Biot's theory they have observed reasonably good agreement between the predicted and measured frequency-dependent coefficients at ultrasonic frequencies, for all three body wavemodes.…”
Section: Materials Characterization (Inverse Problems)mentioning
confidence: 55%
“…For the estimation of E and ν we use f = 820 Hz, corresponding with the (frequency-independent) results in Figure 7.2, because the pSt-wave does Table 7.1: Material parameters as used for water-saturated QF20 porous material. We have measured the magnitudes of ρs, φ and k 0 ourselves; the other values are taken from (Johnson et al, 1994). The values of E and ν have been calculated from those of K b and G. give unique minima in the (E, ν)-domain, exactly at the E-and ν-values of the QF20 (Table 7.1).…”
Section: Porous-medium Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption may not be correct for unconsolidated sand. The generalized moduli formulas appear correct when the grains are bonded [22], but the "bonding" of sand grains may include sliding friction and/or a fluid-reinforced frame [7,11]. Finding good formulas for intermediate moduli of sandy sediments is a task for future work.…”
Section: Modulimentioning
confidence: 99%
“…Johnson et al [22] observed slow compression waves in consolidated fluidsaturated porous media, e.g., fused glass beads (called "Ridgefield Sandstone" even though it was man-made) and ceramic water filters (QF-20), and calculated for the first time all of the input parameters necessary for a complete description of the acoustic properties of all the modes over the entire frequency spectrum.…”
Section: Observations Of Biot Wavesmentioning
confidence: 99%